Okhai-centre for empowerment : refashioning the lives of rural women - Verma, Sanjay, (SAGE Knowledge. Cases., 2017)
In 2002, Tata Chemicals Society for Rural Development (TCSRD) started a handicraft development project in Okhamandal, a region in the western part of the Gujarat state of India, with an objective to provide an additional source of income to its women. Self Help Groups (SHGs) were formed in the villages of Okhamandal, and the members of these groups produced handicrafts like mirror work, patchwork and embroidery. Over the 13 years of its existence, Okhai has grown into an empowering brand, with over 450 women benefiting from this program currently. They earn a monthly income in the range of INR 500-5,000 depending on the time spent working. The initiative has made a huge difference to the lives of rural women. It has not only helped them to become wage earners but also spread awareness about the traditional crafts of the region. Taking this programme to the national level, TCSRD is now promoting it as a new organisation: Okhai - Centre for Empowerment.